Contrast Dispersal Patterns as a Predictor of Clinical Outcome With Transforaminal Epidural Steroid Injection for Lumbar Radiculopathy - Paidin, Mark; Hansen, Pamela; McFadden, Molly; Kendall, Richard (PM & R, 2011)
To assess the relationship between epidural contrast dispersal patterns from lumbar transforaminal epidural steroid injections (TFESIs) and both immediate- and short-term pain reduction. We also investigated the effect of the grade of nerve root compression on contrast dispersal pattern and pain reduction. Retrospective review of data from a previous prospective study of outcomes after TFESI. Academic spine and musculoskeletal clinic. Thirty-eight subjects who underwent single-level lumbar TFESI for unilateral lumbar radicular pain. A retrospective assessment of a digital database of TFESIs for unilateral lumbar radicular pain. Type of contrast pattern was analyzed by 2 physiatrists as type I (tubular appearance); type II (nerve root visible as a filling defect); or type III (cloudlike appearance). Grade of nerve root compression on magnetic resonance also was analyzed by 2 physiatrists as grade I abutment, grade II displacement, or grade III entrapment. Effect of type of contrast pattern and grade of nerve root compression on change in Numeric Pain Rating Scale (NPRS) at time of injection (T1), 2 weeks after (T2), and 2 months after (T3). Mean decrease in NPRS at all time points was statistically significant with both types I and III contrast dispersal patterns. Groups with grades II and III nerve root compression had statistically significant reductions in NPRS at all time points. In this retrospective review we found that TFESIs can have an immediate beneficial effect on pain regardless of contrast pattern type or grade of nerve root compression. Subjects with higher grades of nerve root compression and a type I or III contrast pattern have significantly greater reductions in pain at 15 minutes, 2 weeks, and 2 months. Our findings are limited by methodological restrictions, and further confirmation with a prospective trial to review other possible associated factors is recommended.